"تصميم وإنجاز جهاز قياس المواد المذابة TDSلوصف صلاحية المياه" - زغيب, عبد العالي; ميلودي, الحبيب; تجيني, محمد العالي; بوهني, نور الدين; دبار, الطاهر (جامعة الشهيد حمه لخضر الوادي, 2023)
"تحتوي مياه الشرب حول العالم على العديد من العناصر في شكل أملاح ذائبة أو مواد عالقة ، سواء كانت مياه سطحية، جوفية أو حتى مياه امطار الامر الذي استلزم وضع معايير لقياس وفحص جودة هذه المياه. حاليا، و مع التقدم العلمي و التكنولوجي أخذت أجهزة القياس الإلكترونية و الرقمية مكان وسائل القياس التقليدية لما تمتاز به من دقة و مرونة في التعامل من ناحية و سهولة الاستخدام و الصيانة من ناحية أخرى. تم القيام في هذا المشروع بدراسة تصميم وإنجاز جهاز قياس اجمالي المواد الصلبة الذائبة TDSلوصف صلاحية المياه. في البداية، تم تقديم دراسة نظرية حول الحساسات و مفهوم TDS وما يتعلق به من مصطلحات، و من ثم انشاء وتصميم نموذج عبر برنامج المحاكاة Proteusلجهاز قياس TDSوإضافة ميزة قياس درجة الحرارة، الرطوبة و الزمن الحقيقي. تم شرح الوحدات و المكونات اللازمة، ثم ملاحظة واختبار المتغيرات و مناقشة نتائج المحاكاة. بعد ذلك، تم إنجاز المشروع باستعمال القطع الحقيقية في المخبر وفحص و تجريب الجهاز باستخدام عدة انواع من المياه و المحاليل المحضرة مخبريا. أظهرت النتائج المحصل عليها وجود تطابق مع نتائج المحاكاة بدقة مقبولة وأظهرت امكانية استعمال واستغلال الجهاز في تطبيقات معايرة و مراقبة جودة المياه." "Around the world, drinking water contains many elements in dissolved salts form or suspended matters, whether it is surface water, groundwater or even rain water, which required to set standards for water quality measurement and testing. Currently, with scientific and technological progress, electronic and digital measuring instruments have replaced the traditional measuring methods, due to their accuracy and flexibility in handling on the one hand, and the ease of use and maintenance on the other hand. In this project, a study was carried out for design and implementation of total dissolved solids (TDS) measurement system to describe water quality. At the beginning, a theoretical study on sensors, the concept of TDS and related terms has been presented, then a model of TDS measurement system was designed and created using Proteus ISIS. Also temperature, humidity measurement, and real time has been added. The necessary units and components have been explained. Then observing, testing the variables and discussing of simulation results. After that, the project was realized by using the real parts in the laboratory, examining and testing the device using several types of water and laboratoryprepared solutions. The obtained results showed agreement with the simulation results with acceptable accuracy and showed the possibility of using the device in water quality testing and monitoring applications"
مذكرة ماستر هندسة كيميائيةDes thèses génie chimique
Keywords: اجمالي المواد الصلبة الذائبة، حساس، ،Proteusالزمن الحقيقي; TDS, sensor, Arduino, Proteus, real clock